Effect of heterocycles on field-effect transistor performances of donor-acceptor-donor type small molecules - Chini, Mrinmoy Kumar; Mahale, Rajashree Y.; Chatterjee, Shyambo (Chemical Physics Letters, 2016)
Two D-A-D small molecules comprising triphenylamine and diketopyrrolopyrrole were synthesized having either furan or thiophene connected to the fused lactam ring. In this design, furan/thiophene diketopyrrolopyrrole acts as an acceptor and triphenylamine acts as a donor. Propeller shaped triphenylamine has its effect on packing, processability and plays a vital role in determining the pi-pi molecular orbital stacking in such compounds and thus the mobility of charge carriers. With TDPPT and FDPPT, maximum hole carrier mobility obtained is 2.88 x 10(-3) cm(2) V-1 s(-1) and 1.60 x 10(-3) cm(2) V-1 s(-1), respectively using bottom gate bottom contact field-effect transistor. (C) 2016 Elsevier B.V. All rights reserved.

Effect of side-chain functionality on the organic field-effect transistor performance of oligo(p-phenylenevinylene) derivatives - Chini, Mrinmoy Kumar; Chatterjee, Shyambo (Journal of Applied Polymer Science, 2017)
In order to observe the effects of the substitution of electronegative flourine with aromatic groups in oligo(p-phenylenevinylene) compounds on their packing, morphology, and charge carrier mobility, we have synthesized napthol-substituted oligo(p-phenylenevinylene) compounds and examined their solubility, redox properties, thin film morphologies, and charge carrier properties. To date, very few examples of conjugated oligomers bearing napthol side groups have been reported in the literature. After annealing at 150 degrees C, the mobility of S1, S2, and S3 was 4.0x10(-2) cm(2) V-1 s(-1), 1.2x10(-2) cm(2) V-1 s(-1), and 2.6x10(-3) cm(2) V-1 s(-1), respectively. (c) 2017 Wiley Periodicals, Inc.